AMYGDALA, PREFRONTAL CORTEX, AND HEMISPHERIC SPECIALIZATION IN EMOTIONAL EXPERIENCE AND EXPRESSION - Sánchez-Navarro, Juan Pedro; Román, Francisco (Anales de Psicología / Annals of Psychology, 2004)
Data coming from neuroscience studies point to several structures, both subcortical and cortical, related to emotional behavior. Either the data deriving from research employing non-damaged subjects and those coming from brain damage studies and functional neuroimage techniques point to the amygdala as a key structure in emotion, particularly in the response to negative stimuli. In addition, a growing body of research has found that different regions of the prefrontal cortex (e.g., orbitofrontal and medial) are implied in emotion. Hence, we will review in this paper the data about the relationship of these structures in the emotional behaviour and the hemispheric specialization.